Association of chronic Chagas cardiomyopathy stages with obstructive sleep apnea and excessive daytime sleepiness: a cross-sectional study - Cruz, Luana F.; Oliveira, Liliane F. A.; Pache de Faria, Isabela Guimarães; Viana, Vinicius C.; Silva, Bruno M. F.; Serrano, Caroline P.; Paes, Lucia R. N. B.; Mediano, Mauro F. F.; Hasslocher-Moreno, Alejandro M.; Valete, Cláudia Maria (Frontiers in Medicine, 2025)
IntroductionChagas disease (CD) remains a significant cause of morbidity and mortality in Latin America. Chronic Chagas cardiomyopathy (CCC) is the most severe clinical form. Obstructive sleep apnea (OSA), a highly prevalent sleep-related breathing disorder, is associated with adverse cardiovascular and metabolic outcomes, yet its clinical relevance in CD remains poorly understood. This study aimed to examine the association between the stages of CCC with the OSA risk and excessive daytime sleepiness (EDS) in patients with CD.MethodsThis cross-sectional observational study included patients with chronic CD. OSA risk was assessed using the STOP-BANG questionnaire; EDS was measured by the Epworth Sleepiness Scale. CCC staging followed the 2nd Brazilian Consensus on CD. Categorical variables were compared using Pearson’s chi-square test and continuous variables with ANOVA. Logistic regression models were fitted to explore associations between CCC stages with OSA risk and EDS.ResultsA total of 133 patients (35.3% men; mean age 67.1 years) were included. Of these, 34.6% had no CCC, 49.6% were CCC stages A/B1, and 15.8% were stages B2/C. Of the 130 participants who completed the STOP-Bang questionnaire, 19.2% were at low risk for OSA (score ≤2), while 80.8% were at intermediate or high risk (score >2). EDS (Epworth Sleepiness Scale >10) was identified in 19.6% of participants. No significant associations were found between CCC stages with either OSA risk or EDS.ConclusionDespite a high prevalence of OSA risk among patients with CD, no association was observed between CCC severity and OSA risk or EDS.